Traditional ecological knowledge of the bird traders on bird species bird naming, and bird market chain: A case study in bird market Pasty Yogyakarta, Indonesia - JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR; DEDE MULYANTO; RACHMAN LATIF ALFIAN; Ruhyat Partasasmita (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Iskandar J, Iskandar BS, Mulyanto D, Alfian RL, Partasasmita R. 2020. Traditional ecological knowledge of the bird traders on bird species bird naming, and bird market chain: A case study in bird market Pasty Yogyakarta, Indonesia. Biodiversitas 21: 2586-2602. The bird-keeping in Indonesian society has been popular for a long time. Because the demand for birds has increased in an urban area, plenty of bird species are predominantly traded in urban bird markets. Bird market is a place for selling and buying various birds. The rise of bird trade in the bird markets in many regions of Indonesia has provided social and economic benefits for many people. But in addition to providing many benefits, the plentiful bird trade in bird markets that are not well managed is very worrying about the extinction of various bird species in rural ecosystems. This paper aimed to elucidate the Traditional Ecological Knowledge (TEK) of bird traders on bird species traded, bird naming and folk classification of bird species, and market chain system based on a case study in bird market of Pasty, Yogyakarta. The method used in this study was a qualitative method with the ethnoornithological approach. The results of the study showed that it was documented 106 bird species representing 40 families traded in the Pasty bird market. The common local names and folk bird classification are culturally based on bird vocalization, special colors, morphological characteristics, special habitats, involvement in bird song contests, flying racing competitions, selling prices, and wilderness. Most wild and semi-bird species are traded in the Pasty bird market are predominantly supplied from a rural ecosystem.